2014
DOI: 10.3892/mmr.2014.2181
|View full text |Cite
|
Sign up to set email alerts
|

Monoglucosyl-rutin as a potential radioprotector in mammalian cells

Abstract: In the present study, the role of monoglucosyl-rutin as a potential radioprotector was investigated using mammalian cell culture models. Cell survival and DNA damage were assessed using colony formation, sister chromatid exchange and γH2AX assays. It was demonstrated that monoglucosyl-rutin was able to increase cell survival when exposed to ionizing radiation, possibly by decreasing the amount of base damage experienced by the cell. However, the present study also demonstrated that, despite monoglucosyl-rutin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…It has been shown that rutin prevents UV-induced changes in skin cell membrane function and, by inhibiting the activity of cyclooxygenases and lipoxygenases as well as non-enzymatic lipid mediators generation, inhibits pro-inflammatory signaling [20,21]. Moreover, rutin exerts cytoprotective effects on cells exposed to various types of physical factors by substantially increasing their viability [22,23]. Additionally, rutin exerts cytoprotective effects on cells exposed to different types of radiation by substantially increasing their viability [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that rutin prevents UV-induced changes in skin cell membrane function and, by inhibiting the activity of cyclooxygenases and lipoxygenases as well as non-enzymatic lipid mediators generation, inhibits pro-inflammatory signaling [20,21]. Moreover, rutin exerts cytoprotective effects on cells exposed to various types of physical factors by substantially increasing their viability [22,23]. Additionally, rutin exerts cytoprotective effects on cells exposed to different types of radiation by substantially increasing their viability [16].…”
Section: Introductionmentioning
confidence: 99%
“…Rutin is a flavonoid found in plant extracts, and inhibits the activities of cyclooxygenases and lipoxygenases, thereby reducing pro-inflammatory processes [8]. Moreover, rutin exerts cytoprotective effects on cells exposed to various types of radiation by substantially increasing their viability [79]. So far, the interaction of orally administered rutin with ascorbic acid has been demonstrated in terms of their antiinflammatory and vascular sealing actions [4,51].…”
Section: Introductionmentioning
confidence: 99%
“…The CHO10B2 (wild-type), V3 (protein kinase DNA-activated catalytic polypeptide deficient) (12) (16). Heavy ion irradiation was performed at the National Institute of Radiological Sciences (Chiba, Japan).…”
Section: Methodsmentioning
confidence: 99%